2022
DOI: 10.3390/polym14224924
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Biodegradable Polymers and Their Biological Applications: A Brief Review

Abstract: The rising significance of the field of biopolymers has driven the rapid progress of this distinctive class of polymeric materials in the past decades. Biodegradable polymers have acquired much attention because they play an essential role in humans’ lives due to their specific tunable electrical conductivity and biodegradability characteristics, making them fascinating in many applications. Herein, we debated the recent progress in developing biodegradable polymers and their applications. Initially, we introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 93 publications
0
17
0
Order By: Relevance
“…One study demonstrated that the insertion of a cysteine amino acid in HVR5 of the hexon protein, enabled the linkage of polymers via thioether links, examples including HPMA [289] and PEG [290] (which as described is no longer very useful beyond proof of concept). However, the potential in this strategy lies in the versatility: As new polymers emerge in time [291], they could likely all be engineered to attach to these Ad vectors.…”
Section: Chemical Shieldingmentioning
confidence: 99%
“…One study demonstrated that the insertion of a cysteine amino acid in HVR5 of the hexon protein, enabled the linkage of polymers via thioether links, examples including HPMA [289] and PEG [290] (which as described is no longer very useful beyond proof of concept). However, the potential in this strategy lies in the versatility: As new polymers emerge in time [291], they could likely all be engineered to attach to these Ad vectors.…”
Section: Chemical Shieldingmentioning
confidence: 99%
“…Controlled cell degradation is important for gel breakdown into non-toxic products, which is key to maintaining long-term drug release and reducing side effects Furthermore, the scalable mechanism of biopolymer gels is important because it can mimic native tissue and withstand physiological stress. This flexibility makes them useful for a variety of biomedical applications, including clinical and diagnostics [15].…”
Section: Properties and Characteristics Of Biopolymer Gelsmentioning
confidence: 99%
“…Over the past few years, there has been a growing interest in natural polymers sourced from renewable biomass resources, such as cellulose, as they offer numerous advantages like affordability, recyclability, and biodegradability [1][2][3]. Continuous population growth and industrialization resulted in a high abundance of agricultural residues, which present a valuable opportunity for the upgrading of waste into cellulose with nano aspects, which offers a promising avenue for advancing sustainability and creating innovative solutions across multiple industries.…”
Section: Introductionmentioning
confidence: 99%